Combat exposure and co-occurring mental health problems in UK Armed Forces personnel. (3rd September 2022) - Chui, Zoe; Fear, Nicola T.; Greenberg, Neil; Jones, Norman; Jones, Edgar; Goodwin, Laura
ABSTARCT: Background: Mental disorders and alcohol misuse are often comorbid, and this comorbidity is more common in those who develop mental disorders following exposure to traumatic events. Aims: To investigate the relationship between combat exposure and operational role (support versus combat) with mental disorders and associated comorbidity in a UK military cohort. Methods: 4896 participants from a UK military cohort reported their operational role and frequency of exposure to combat events during deployment. Outcome measures included self-reported post-traumatic stress disorder, common mental disorder and alcohol misuse. Results: Personnel reporting higher levels of combat exposure were more likely to meet criteria for two or more co-occurring mental disorders (odds ratio [OR] 3.90, 95% confidence interval [CI] 2.73–5.58). While having a combat role increased the risk of developing co-occurring disorders compared to having a support role (OR 1.67, 95% CI 1.26–2.23), this effect diminished following adjustment for variables including combat exposure (OR 0.89, 95% CI 0.62–1.27). Conclusions: Combat exposure may play a greater role in the development of comorbid mental disorders than operational role, i.e. job title. Clinicians treating military personnel should be alert to the increased risk of comorbid mental disorders and alcohol misuse among those with a history of combat exposure.